Diversity of strategies for escaping reactive oxygen species production within photosystem I among land plants: P700 oxidation system is prerequisite for alleviating photoinhibition in photosystem I. Issue 1 (24th May 2017) - Takagi, Daisuke; Ishizaki, Kimitsune; Hanawa, Hitomi; Mabuchi, Tomohito; Shimakawa, Ginga; Yamamoto, Hiroshi; Miyake, Chikahiro
Abstract : In land plants, photosystem I (PSI) photoinhibition limits carbon fixation and causes growth defects. In addition, recovery from PSI photoinhibition takes much longer than PSII photoinhibition when the PSI core‐complex is degraded by oxidative damage. Accordingly, PSI photoinhibition should be avoided in land plants, and land plants should have evolved mechanisms to prevent PSI photoinhibition. However, such protection mechanisms have not yet been identified, and it remains unclear whether all land plants suffer from PSI photoinhibition in the same way. In the present study, we focused on the susceptibility of PSI to photoinhibition and investigated whether mechanisms of preventing PSI photoinhibition varied among land plant species. To assess the susceptibility of PSI to photoinhibition, we used repetitive short‐pulse (rSP) illumination, which specifically induces PSI photoinhibition. Subsequently, we found that land plants possess a wide variety of tolerance mechanisms against PSI photoinhibition. In particular, gymnosperms, ferns and mosses/liverworts exhibited higher tolerance to rSP illumination‐induced PSI photoinhibition than angiosperms, and detailed analyses indicated that the tolerance of these groups could be partly attributed to flavodiiron proteins, which protected PSI from photoinhibition by oxidizing the PSI reaction center chlorophyll (P700) as an electron acceptor. Furthermore, we demonstrate, for the first time, that gymnosperms, ferns and mosses/liverworts possess a protection mechanism against photoinhibition of PSI that differs from that of angiosperms.